Tawhid in Arabic Persfective: Semantic Studies - Mardhatillah Syahril; Salamuddin Salamuddin (Edumaspul: Jurnal Pendidikan, 2023)
This research was conducted to examine the meaning of the word Tawhid in the Arabic language perspective and understand in depth the nature of the word Tawhid in various semantic linguistic perspectives of the Arabic language. This research is a qualitative research with the method used, namely the descriptive method of analysis. The method is used in analyzing the word Tawhid in various perspectives, especially in the Arabic perspective. The meaning of Tawhid contained in several Arabic dictionaries is very varied. Researchers use semantic analysis derived from several dictionaries, sharaf books, and the perspectives of experts who can be analyzed that the word "توحيد" is isim masdar, and is called the word "توحيد" because the true meaning of the word tawhid is to discuss God. In Arabic, the word Allah is isim so it can be said, the word tawhid is given to Allah. Therefore, the science of tawhid is a science that includes a discussion of the dzat-dzat of Allah, the asthma of Allah and af'al Allah and also the science that believes in the existence of Allah. The researchers concluded that the basic meaning of the word Tawhid is to worship God with the total belief that there is "There is no God but Allah".